This local band! Celebrity culture of Jawa Arek in Yowis Ben tetralogy - Wibowo, Nimas (Jurnal Studi Komunikasi, 2025)
This paper analyses the representation of the celebrity phenomenon in the Yowis Ben tetralogy (2018, 2019, 2021), which has become a fundamental aspect of modern Indonesian film. The researcher used a qualitative narrative analysis approach to examine how celebrity culture is portrayed in these films. This analysis examined story structure, character development, and visual components, highlighting the journey of a group of young individuals from the Javanese Arek Culture as they strive for popularity while preserving their cultural identity. The results indicate that this tetralogy positions celebrity culture as a remedy for desires related to social status, physical allure, affluence, and influence. The celebrity persona depicted in these films is intricately linked to the context of Javanese Arek culture, particularly in Malang, Indonesia. Cultural components, including language and intricate characters, enhance the representation of celebrity production. These films explain the intricacies of celebrity life while examining the motivations for attaining recognition, the techniques employed to gain it, the efforts to sustain a public persona, and the challenges encountered by celebrities.